Frequency of Urinary Tract Infections (UTI) in Neonates with Indirect Hyperbilirubinemia - Muhammad Matiullah; Mobeen, Amina; Khalid, Eisha; Bashir, Roshaan; Masood, Amna; Muhammad Sohaib (Indus Journal of Bioscience Research, 2025)
Background: A significant percentage of neonatal hospital admissions are caused by neonatal jaundice, one of the most prevalent clinical disorders during the neonatal era. Some newborns may experience pathological jaundice because of underlying illnesses like infections, even though the majority of instances are physiological. One significant but frequently disregarded cause of indirect hyperbilirubinemia in neonates is urinary tract infection (UTI). Jaundice is frequently the only sign of a UTI, which can cause a delay in diagnosis if the necessary tests are not carried out. Methodology: Over the course of six months, this descriptive cross-sectional study was carried out in a tertiary care hospital’s pediatric ward and neonatal intensive care unit (NICU). Non-probability consecutive sampling was used to include 151 infants with indirect hyperbilirubinemia. A standardized proforma was used to record demographic and clinical information such as age, gender, gestational age, and birth weight. Under aseptic conditions, sterile catheterization was used to collect urine samples, which were then examined using urine microscopy and culture. SPSS version 25 was utilized for data entry and analysis. For categorical variables, frequencies and percentages were computed, and associations between variables were evaluated using the Chi-square test, where a p-value of less than 0.05 was deemed statistically significant. Results: 94 (62.3%) of the 151 newborns were male, and 57 (30.7%) were female. While 122 neonates (80.8%) showed no signs of a urinary tract infection, 29 neonates (19.2%) developed a UTI. Escherichia coli was the most frequently isolated organism (65.5%), followed by Proteus mirabilis (10.4%) and Klebsiella pneumoniae (24.1%). Preterm and low birth weight neonates had a slightly higher prevalence of UTI, but the differences were not statistically significant. Conclusion: According to the study, infants who arrive with indirect hyperbilirubinemia are comparatively likely to have urinary tract infections. Neonates with chronic or unexplained jaundice should be screened for urinary tract infections to help with early identification and avoid consequences.